2012
DOI: 10.1016/j.celrep.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Potential Marks the Emergence of Definitive Hematopoietic Progenitors in Human Pluripotent Stem Cell Differentiation Cultures

Abstract: The efficient generation of hematopoietic stem cells from human pluripotent stem cells is dependent on the appropriate specification of the definitive hematopoietic program during differentiation. In this study, we used T lymphocyte potential to track the onset of definitive hematopoiesis from human embryonic and induced pluripotent stem cells differentiated with specific morphogens in serum- and stromal-free cultures. We show that this program develops from a progenitor population with characteristics of hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
436
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(470 citation statements)
references
References 56 publications
19
436
1
2
Order By: Relevance
“…This is reflected in the difficulty to generate bona fide HSCs de novo from ES/iPS cells [50,85,[91][92][93], or through direct reprogramming [94,95]. This indicates that critical components of EHT, responsible for regulating the hematopoietic nature of these cells are missing in these culture systems and indicate the importance of understanding the cellular, molecular and niche requirements for EHT in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the difficulty to generate bona fide HSCs de novo from ES/iPS cells [50,85,[91][92][93], or through direct reprogramming [94,95]. This indicates that critical components of EHT, responsible for regulating the hematopoietic nature of these cells are missing in these culture systems and indicate the importance of understanding the cellular, molecular and niche requirements for EHT in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The CD34 + CD43 + haematopoietic progenitors give rise to a broad range of erythroid and myeloid lineages (Choi et al, 2012;Kennedy et al, 2012;Ng et al, 2016), reminiscent of the broad potential of the yolk sac-derived erythro-myeloid progenitor (EMP) described in the mouse that transiently seeds the foetal liver (McGrath et al, 2015). Although EMP-type haematopoiesis has not been formally characterised in human embryos, kinetic studies report a rapid transition of clonogenic cells from the yolk sac to the foetal liver at around 5 weeks of gestation (Migliaccio et al, 1986).…”
Section: The Generation Of Yolk Sac-like Haematopoietic Lineagesmentioning
confidence: 99%
“…It was only later that a series of studies shed light on the role of mesoderm patterning for both the suppression of primitive haematopoiesis and for the support of definitive haematopoietic lineages. Following an initial period of BMP4-based mesoderm induction, brief inhibition of activin (Kennedy et al, 2012), or provision of a WNT agonist (Gertow et al, 2013) were sufficient to inhibit the erythroid-biased primitive programme. Importantly, activin inhibition (Kennedy et al, 2012), WNT stimulation (Sturgeon et al, 2014) or a combination of the two (Ng et al, 2016) from days 2-4 of in vitro differentiation also resulted in a bias towards definitive haematopoietic lineages, as defined by the capacity to generate T lymphocytes (Kennedy et al, 2012;Sturgeon et al, 2014).…”
Section: Mesoderm Induction and Patterningmentioning
confidence: 99%
“…With regard to multipotency, almost all hematopoietic cell types can be generated from hESCderived hematopoietic precursors, including erythrocytes, 13 megakaryocytes, 14 granulocytes, monocytes, 15 NK cells 16 and T cells. 17,18 Although, to our knowledge, it has not been demonstrated that a single hESC-derived hematopoietic precursor cell is able to form all of the aforementioned cell types, the absence of these reports may be due to technical issues associated with precursor cells of limited proliferative capacity. The fact that T cells can be generated from fetal HPC does not in itself prove the presence of multipotent progenitors or HSC, since it has been shown that T cells can be generated from YS precursors that arise before HSC are generated.…”
Section: Discussionmentioning
confidence: 78%